Efficacy and safety of triazoles versus echinocandins in the treatment of invasive aspergillosis: A meta-analysis - Uzelac, Sanja M.; Živković Zarić, Radica S.; Radovanović, Milan R.; Ranković, Goran Ž.; Janković, Slobodan M. (Vojnosanitetski pregled, 2021)
Backgroun/Aim. Although majority of guidelines recommend triazoles (voriconazole, posaconazole, itraconazole and isavuconazole) as first-line therapeutic option for treatment of invasive aspergillosis, echinocandins (caspofungin, micafungin and anidulafungin) are also used for this purpose. However, head-to-head comparison of triazoles and echinocandins for invasive aspergillosis was rarely target of clinical trials. The aim of this meta-analysis was to compare efficacy and safety of triazoles and echinocandins when used for treatment of patients with invasive aspergillosis. Methods. This meta-analysis was based on systematic search of literature and selection of high-quality evidence according to pre-set inclusion and exclusion criteria. The literature search was made for comparison of treatment with any of triazoles (isavuconazole, itraconazole, posaconazole or voriconazole) versus any of echinocandins (caspofungin, anidulafungin or micafungin). The effects of triazoles (itraconazole, posaconazole or voriconazole) and echinocandins (caspofungin, anidulafungin or micafungin) were summarized using RevMan 5.3.5 software, and heterogeneity assessed by the Cochrane Q test and I² values. Several types of bias were assessed, and publication bias was shown by the funnel plot and Egger’s regression. Results. Two clinical trials and three cohort studies were included in this meta-analysis. Mortality in patients with invasive aspergillosis who were treated with triazoles was significantly lower than in patients treated with echinocandins [odds ratio 0.29 (0.13, 0.67)], and rate of favorable response (overall treatment success) 12 weeks after the therapy onset was higher in patients treated with triazoles [3.05 (1.52, 6.13)]. On the other hand, incidence of adverse events was higher with triazoles than with echinocandins in patients treated for invasive aspergillosis [3.75 (0.89, 15.76)], although this difference was not statistically significant. Conclusion.Triazoles (voriconazole in the first place) could be considered as more effective and somewhat less safe therapeutic option than echinocandins for invasive aspergillosis: However, due to poor quality of studies included in this meta-analysis, definite conclusion should await results of additional, well designed clinical trials.
Keywords: aspergillosis; triazoles; echinocandins; meta-analysis